"It Was the Only Thing I Could Hold Onto, But…": Receiving a Letter of Condolence After Loss of a Loved One in the ICU. Issue 12 (December 2017) - Kentish-Barnes, Nancy; Cohen-Solal, Zoé; Souppart, Virginie; Galon, Marion; Champigneulle, Benoît; Thirion, Marina; Gilbert, Marion; Lesieur, Olivier; Renault, Anne; Garrouste-Orgeas, Maïté; Argaud, Laurent; Venot, Marion; et al.
Abstract : Objectives: Family members of patients who die in the ICU often remain with unanswered questions and suffer from lack of closure. A letter of condolence may help bereaved relatives, but little is known about their experience of receiving such a letter. The objective of the study was to understand bereaved family members' experience of receiving a letter of condolence. Design: Qualitative study using interviews with bereaved family members who received a letter of condolence and letters written by these family members to the ICU team. This study was designed to provide insight into the results of a larger randomized, controlled, multicenter study. Setting: Twenty-two ICUs in France. Subjects: Family members who lost a loved one in the ICU and who received a letter of condolence. Measurements and Main Results: Thematic analysis was used and was based on 52 interviews and 26 letters. Six themes emerged: 1) a feeling of support, 2) humanization of the medical system, 3) an opportunity for reflection, 4) an opportunity to describe their loved one, 5) continuity and closure, and 6) doubts and ambivalence. Possible difficulties emerged, notably the re-experience of the trauma, highlighting the absence of further support. Conclusions: This study describes the benefits of receiving a letter of condolence; mainly, it humanizes the medical institution (feeling of support, confirmation of the role played by the relative, supplemental information). However, this study also shows a common ambivalence about the letter of condolence's benefit. Healthcare workers must strive to adapt bereavement follow-up to each individual situation. Abstract : Supplemental Digital Content is available in the text.